Effect of Pre-harvest Calcium Chloride Spray Combined with Post-harvest Salicylic Acid Treatment on Storage Quality and Fruit Softening of Sweet Cherries - Binbin LI; Zhonghong WU; Jinqiang ZHANG; Huijing GUO; Xinwen JIN; Pengcheng LI (Shipin gongye ke-ji)
This study examined the impact of calcium chloride (CaCl2) spray prior to harvest, salicylic acid (SA) post-harvest, and the combination of CaCl2+SA treatments on the quality indicators, cell wall components, and cell wall-degrading enzymes of 'Meizao' sweet cherries during cold storage. Additionally, the study employed transmission electron microscopy to observe the ultrastructure of cells. The findings demonstrated that in comparison to the control group (distilled water treatment), the CaCl2, SA, and CaCl2+SA treatments were capable of postponing the decline in soluble solids, titratable acidity, firmness, and L* value of fruit flesh. Additionally, these treatments were able to maintain higher levels of ascorbic acid, total phenolics, and anthocyanin. The treatments inhibited the activities of amylase, Cx, PG, and β-glucosidase, delayed the degradation of starch, pro-pectin, and cellulose content, reduced the accumulation of soluble pectin content, and maintained the integrity of the fruit cell structure. The CaCl2+SA treatment demonstrated the most pronounced effect. The results of the correlation analysis indicated a significant correlation between the main quality indicators and cell wall components with the activities of cell wall-degrading enzymes (P<0.001). Furthermore, the principal component analysis revealed that there were notable differences in storage quality among the treatment groups, with the CaCl2+SA treatment group exhibiting the highest overall score. In conclusion, the application of CaCl2 prior to harvest, in conjunction with a post-harvest SA treatment, has been demonstrated to effectively retard the softening process of sweet cherries following harvest, thereby maintaining their storage quality.